The historical development of the University of the Philippines and Siliman University dual athletic meet (1922-1968) - Tiamzon, Mercedita S. 1936- (Quezon City s.n., 1972)
The historical development of the dual athletic meet between the University of the Philippines and Silliman University was traced. Its role in the promotion of sports and athletics was analyzed.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Silliman University -- Athletics -- History; Philippines -- Athletic -- History